Innovations in Islamic Education Management within the University Context: Addressing Challenges and Exploring Future Prospects - Nilna Azizatus Shofiyyah; Tedy Sutandy Komarudin; Moch. Sya'roni Hasan (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This research explores innovation in the management of Islamic education in higher education institutions, along with the associated challenges and prospects. Its objective is to comprehend the challenges of implementing innovation in Islamic education management and assess its prospects. The research methodology employed is a qualitative literature study. The researchers gathered and analyzed various literature sources to gain a more profound understanding. The research findings reveal challenges such as a lack of comprehension, resistance to change, resource limitations, and the conflict between tradition and modernity. Nonetheless, there exist opportunities for developing new adaptive and relevant approaches. Innovation in Islamic education management yields benefits in the form of enhanced learning quality, student skill development, operational efficiency, and increased reputation and competitiveness of higher education institutions. Collaboration and strong leadership serve as pivotal factors for successfully confronting challenges and expanding innovation prospects.